The impacts of physical, psychological, and environmental factors on employees job satisfaction among public accounting professionals in Malaysia / Sze Yin Koh, Tze San Ong and Adedeji Babatunji Samuel. - Sze, Yin Koh; Tze, San Ong; Samuel, Adedeji Babatunji (Accounting Research Institute and UiTM Press, Universiti Teknologi MARA, 2017)
The issue of employees’ job satisfaction among public accounting professionals has become a very critical issue for employers as it might affect the quality, productivity, and sustainability of public accounting firms in today’s economy and business environment. Therefore, this research was attempted to provide insights on the variables influencing job satisfaction. Besides that, this research paper was also aimed at exploring whether job satisfaction plays a role in mediating the relationship between the six factors, organizational commitment, and employees’ loyalty. For data collection, a structured questionnaire was developed and a total of 103 responses were received from accountants, auditors, tax advisors, consultants and secretaries. Furthermore, the four step regression analysis was employed in this study in order to evaluate the mediating role of job satisfaction. The results have revealed that all the six variables (remuneration, relations with supervisors & co-workers, job security, job promotion, management/leadership style, and organizational culture) are significant factors in explaining the job satisfaction among public accounting professionals. Moreover, the findings have also shown that job satisfaction significantly mediates not only the relationship between supervisors & co-workers and organizational commitment, but also the relationship between job security and employees’ loyalty. These results have provided insight for public accounting firms in overcoming the issues of job satisfaction among their employees.